Pengaruh Independensi, Integritas, Kompetensi, dan Struktur Audit terhadap Kualitas Audit Kantor Inspektorat - Gita, Anak Agung Ngurah Agung Wira; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi, 2018)
Inspectorate in carrying out its profession must pay attention to the quality of its audit. To produce good audit quality, an auditor should consider the factors that affect audit quality. Independence, Competence, Integrity, and Audit Structure are the factors that affect audit quality. The purpose of this study is to know empirically the influence of Independence, Competence, Integrity and Audit Structure of Audit Quality. The research was conducted in 4 District / City Inspectorate Offices in Bali Province. The number of samples taken as many as 60 auditors, Data collection methods used in this study is a survey method with questionnaire techniques. Data analysis technique used is Multiple Linear Regression Analysis. Based on the analysis results found that Independence, Competence, Integrity, and Audit Structure have a significant positive effect on audit quality. This suggests that an auditor must remain independent, competent, risk-taking, responsible, and knowledgeable about sound auditing procedures.   Keywords: independence, competence, integrity, audit structure, and audit quality